Comparative analysis of foam-only versus carbon-plated advanced footwear technology spikes in distance runners - Wu, Yiwei; Zhang, Haoran; Wang, Shuhan; Lu, Changda; Xing, Qingjun; Tian, Yinshen; He, Dianchen; Sun, Lixin; Shen, Yanfei (Frontiers in Physiology, 2025)
BackgroundAdvanced footwear technology (AFT) spikes are commonly offered in two configurations: foam only and foam combined with a carbon fiber plate. Whether the plate provides additional metabolic or performance benefits over foam-only designs remains uncertain. Therefore, this study compared physiological, biomechanical, and perceptual responses to two commercially available AFT spikes (Nike ZoomX Dragonfly, foam only; Nike Air Zoom Victory, foam plus carbon plate) in trained and national-level distance runners.MethodsThirteen male middle- and long-distance runners (trained, n = 6; national-level, n = 7) completed three randomized 1600-m submaximal trials on an outdoor track at 16 km·h−1 (trained) or 18 km·h−1 (national-level). Running economy (RE) was assessed using a portable gas analyzer (MetaMax 3B-R2); spatiotemporal gait variables were recorded with shoe-mounted sensors (RunScribeTM); and participants rated comfort, cushioning, and perceived performance on a 10-point Likert scale.ResultsIn the national-level group, both foam-only spikes (Dragonfly1, Dragonfly2) produced better RE than the carbon-plated model (Victory1), with no difference between the two foam-only versions. In the trained group, RE did not differ across spikes. Energetic cost paralleled the VO2 findings. For gait parameters, stride length and step frequency were unchanged across conditions in both groups. Whereas contact time in the national-level group was longer in Dragonfly1 than in Dragonfly2 and Victory1, whereas Dragonfly2 and Victory1 did not differ; in the trained group, contact time was unchanged across spikes. Subjectively, across all participants, foam-only spikes were rated more comfortable and more cushioned, whereas perceived performance did not differ between models.ConclusionAt long-distance race paces, foam-only AFT spikes improved RE and were perceived as more comfortable than a plate-integrated spike in national-level athletes. Adding a carbon plate did not guarantee a metabolic benefit and may increase energetic cost when shoe stiffness exceeds an athlete-specific optimum. Spike selection, particularly for track events, should demystify carbon plates and prioritize the individualized selection of shoe stiffness and geometry matched to event distance, running speed, and athlete-specific biomechanics.